TRANSFORMASI KEBIJAKAN KETAHANAN PANGAN INDONESIA: ANALISIS PARADIGMA PEMBANGUNAN SOSIAL LINTAS ERA - Virza Hafidh Adrian; Sofyan Cholid (Social Welfare Study Program, 2026)
Abstract. National food security policies in Indonesia have undergone a dynamic paradigm evolution across leadership eras. This study aims to comparatively analyze the transformation of social protection strategies in the food sector, moving from the residual, commodity-based model under Susilo Bambang Yudhoyono, to the financial inclusion and digitalization-driven approach of the Joko Widodo era, and finally to the promotive-preventive human capital investment strategy within Prabowo Subianto’s Asta Cita framework. Utilizing a descriptive-analytical qualitative method with a documentary study approach based on Scopus data and policy drafts, this research explores the effectiveness of equity, empowerment, and social protection pillars in addressing nutritional deprivation. The findings indicate that despite increased institutional maturity in recognizing the right to food, the efficacy of formal social safety nets remains severely constrained by structural bottlenecks. These obstacles include digital telecommunication infrastructure disparities in Eastern Indonesia, the industrial bias of large-scale projects such as the food estate, and intense agrarian space competition driven by oil palm expansion for B40 biofuel quotas. Consequently, vulnerable groups—including multidimensionally poor households, agricultural laborers, persons with disabilities, and urban marginalized communities—face acute functional precarity, forcing them to rely on local informal moral economy networks to survive. This study recommends stringent cross-sectoral agrarian zoning harmonization, accelerated digital infrastructure deployment, and the integration of local social capital into the national formal food security architecture to achieve universal distributive justice. Keyword: Food Policy; Social Development; Vulnerable Groups; Biofuel; Moral Economy. Abstrak. Kebijakan ketahanan pangan nasional di Indonesia terus mengalami evolusi paradigma yang dinamis lintas periode kepemimpinan. Penelitian ini bertujuan untuk menganalisis secara komparatif transformasi strategi perlindungan sosial pangan dari masa pemerintahan Susilo Bambang Yudhoyono yang bersifat residual-komoditas, era Joko Widodo yang berbasis inklusi keuangan dan digitalisasi, hingga rencana strategis Asta Cita era Prabowo Subianto yang berfokus pada investasi modal manusia secara promotif-preventif. Menggunakan metode kualitatif deskriptif-analitis dengan pendekatan studi dokumen kepustakaan berbasis data Scopus dan draf kebijakan, penelitian ini mengeksplorasi efektivitas pilar pemerataan, pemberdayaan, dan perlindungan sosial dalam mengatasi deprivasi nutrisi. Hasil kajian menunjukkan bahwa meskipun terjadi peningkatan kematangan institusional dalam memandang hak atas pangan, efektivitas jaminan sosial formal masih dihambat oleh tantangan struktural yang masif. Hambatan tersebut meliputi kesenjangan infrastruktur telekomunikasi digital di kawasan timur Indonesia, bias industrialisasi berskala besar melalui proyek lumbung pangan (food estate), serta kompetisi ruang agraria akibat ekspansi komoditas kelapa sawit demi pemenuhan kuota biofuel B40. Akibatnya, kelompok rentan seperti masyarakat miskin multidimensi, buruh tani gurem, penyandang disabilitas, dan komunitas marginal perkotaan mengalami kerentanan fungsional dan terpaksa mengandalkan jaringan ekonomi moral informal lokal untuk bertahan hidup. Penelitian ini merekomendasikan perlunya harmonisasi regulasi zonasi agraria yang ketat, percepatan pemerataan infrastruktur digital, serta integrasi modal sosial lokal ke dalam sistem jaminan sosial pangan nasional demi mewujudkan keadilan distributif yang universal. Kata Kunci: Kebijakan Pangan; Pembangunan Sosial; Kelompok Rentan; Biofuel; Ekonomi Moral.